If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = -42 + 6x Reorder the terms: 12 + 3x = -42 + 6x Solving 12 + 3x = -42 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 3x + -6x = -42 + 6x + -6x Combine like terms: 3x + -6x = -3x 12 + -3x = -42 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -3x = -42 + 0 12 + -3x = -42 Add '-12' to each side of the equation. 12 + -12 + -3x = -42 + -12 Combine like terms: 12 + -12 = 0 0 + -3x = -42 + -12 -3x = -42 + -12 Combine like terms: -42 + -12 = -54 -3x = -54 Divide each side by '-3'. x = 18 Simplifying x = 18
| -6+7r=6+5r | | -7+7r=6+5r | | (-46)-(12)= | | (-x^2+5x-3)+(7x^2+4x+6)= | | 9+10x=-45+x | | 0.02*1.5= | | (49)-(32)= | | 11x+2=4x+37 | | x+20+3x=120 | | (-41)-(-35)= | | 13=5x-3+3x | | (29)-(-15)= | | 6=3x+33 | | 16=w | | 84+6y=-6y | | 4x+12=10x-12 | | 5x+6-2x=9-7x | | 6(3x-2)-4(5x-9)= | | -[4z-(15z+8)]=8+(10z+1) | | 4x^2+5X-124=0 | | 8x-8=-6+7x | | (-19)-(-12)= | | 8x-8=-7+7x | | 42+12x=49+21x+9 | | (10)-(-19)= | | 240=40y-20x | | x^2-400x-1000=0 | | (-18)-(49)= | | 8x+2=3x+22 | | 72=8x+9y | | 2x-5=200-3x | | 3(2x+1)=2(1+3)-1 |